2019
DOI: 10.3847/1538-3881/ab1d51
|View full text |Cite
|
Sign up to set email alerts
|

Extended X-Ray Study of M49: The Frontier of the Virgo Cluster

Abstract: The M49 group, resident outside the virial radius of the Virgo cluster, is falling onto the cluster from the south. We report results from deep XMM-Newton mosaic observations of M49. Its hot gas temperature is 0.8 keV at the group center and rises to 1.5 keV beyond the brightest group galaxy (BGG). The group gas extends to radii of ∼ 300 kpc to the north and south. The observations reveal a cold front ∼ 20 kpc north of the BGG center and an X-ray bright stripped tail 70 kpc long and 10 kpc wide to the southwes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 80 publications
(99 reference statements)
1
16
0
Order By: Relevance
“…The properties of the outskirts of the Northern Clump are similar to those systems listed above, particularly the case of M49 group residing beyond the virial radius of the Virgo Cluster (Su et al 2019). In addition to the stripped tail, a temperature enhancement is noted in front of the cold front in M49, resembling the temperature elevation and surface brightness edge (see Subsection 3.2.2) observed at ∼ 11.25 (673.65 kpc) and 5 (299.4 kpc), respectively in the south of the Northern Clump.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The properties of the outskirts of the Northern Clump are similar to those systems listed above, particularly the case of M49 group residing beyond the virial radius of the Virgo Cluster (Su et al 2019). In addition to the stripped tail, a temperature enhancement is noted in front of the cold front in M49, resembling the temperature elevation and surface brightness edge (see Subsection 3.2.2) observed at ∼ 11.25 (673.65 kpc) and 5 (299.4 kpc), respectively in the south of the Northern Clump.…”
supporting
confidence: 52%
“…This tail feature is often observed in other merging systems as a result of ram pressure stripping. For example, the tail from M86 and M49 as they fall into the Virgo Cluster (Randall et al 2008;Su et al 2019. Also see Su et al 2014Su et al , 2017a, the northeast tail feature observed in A2142 cluster (Eckert et al 2014.…”
mentioning
confidence: 86%
“…Of course, mergers and AGN feedback can work in unison. For instance, in M49, the 2D Fe abundance map derived by Su et al [157] using XMM-Newton (covering a significantly larger field than that in Reference [96] discussed above) suggests both the presence of a metal enriched tail to the southwest, and a metal enhancement aligned with two outer ghost X-ray cavities along the NE-SW axis on smaller spatial scales (see Figure 6). The authors conclude that the tail gas can be traced back to the cooler and enriched gas uplifted from the BGG center by buoyant bubbles, implying that active galactic nucleus outbursts may have intensified the stripping process.…”
Section: -Dimensional Metallicity Mapsmentioning
confidence: 90%
“…The Fe distribution is elongated in the direction of the AGN ghost cavities (denoted by white dashed circles), with an additional extension towards the west/southwest on larger scales, likely related to a ram-pressure or slingshot tail as the galaxy is falling into the Virgo Cluster. Figure reproduced with permission from Reference[157].…”
mentioning
confidence: 99%
“…Encouragingly, some evidence already exists, for example in the Virgo cluster, where samples of dwarfs with r-band magnitudes −17 ≥ M r ≥ −18 show a skewed velocity distribution that has been attributed to a recent group infall event (Lisker et al 2018). Moreover, both systems, Virgo and Fornax have also obvious ongoing group infall in their outskirts, with the M49 group and Fornax A examples, respectively (Binggeli, Tammann & Sandage 1987;Iodice et al 2017;Su et al 2019). However, the detection of older accretion events deeper into the potential well of the clusters and/or groups with smaller masses remains an observational challenge, complicating the direct comparison to theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%